Dose-Response of a Norovirus GII.2 Controlled Human Challenge Model Inoculum. (8th February 2022) - Rouphael, Nadine; Beck, Allison; Kirby, Amy E; Liu, Pengbo; Natrajan, Muktha S; Lai, Lilin; Phadke, Varun; Winston, Juton; Raabe, Vanessa; Collins, Matthew H; Girmay, Tigisty; Alvarez, Alicarmen; et al.
Abstract: Background: Genogroup II noroviruses are the most common cause of acute infectious gastroenteritis. We evaluated the use of a new GII.2 inoculum in a human challenge. Methods: Forty-four healthy adults (36 secretor-positive and 8 secretor-negative for histo-blood group antigens) were challenged with ascending doses of a new safety-tested Snow Mountain virus (SMV) GII.2 norovirus inoculum (1.2 × 10 4 to 1.2 × 10 7 genome equivalent copies [GEC]; n = 38) or placebo (n = 6). Illness was defined as diarrhea and/or vomiting postchallenge in subjects with evidence of infection (defined as GII.2 norovirus RNA detection in stool and/or anti-SMV immunoglobulin G [IgG] seroconversion). Results: The highest dose was associated with SMV infection in 90%, and illness in 70% of subjects with 10 of 12 secretor-positive (83%) and 4 of 8 secretor-negative (50%) becoming ill. There was no association between prechallenge anti-SMV serum IgG concentration, carbohydrate-binding blockade antibody, or salivary immunoglobulin A and infection. The median infectious dose (ID50 ) was 5.1 × 10 5 GEC. Conclusions: High rates of infection and illness were observed in both secretor-positive and secretor-negative subjects in this challenge study. However, a high dose will be required to achieve the target of 75% illness to make this an efficient model for evaluating potential norovirus vaccines and therapeutics. Clinical Trials Registration: NCT02473224. Abstract : We evaluated the use of a new GII.2 inoculum in a human challenge that could facilitate the evaluation of norovirus vaccines and therapeutics and observed high rates of infection and illness in both secretor-positive and -negative subjects.